Markers or metagenomes: sequencing marine eukaryotic DNA for better biodiversity surveys - Nastassia V. Patin; Kathleen J. Pitz; Jacoby D. Baker; Francisco P. Chavez; Kelly D. Goodwin (Metabarcoding and Metagenomics)
Marker gene sequencing (“metabarcoding”) is the primary sequencing approach currently used for molecular biodiversity surveys, but this approach is taxonomically limited and hampered by amplification biases. In contrast, shotgun metagenomes avoid extensive PCR amplification and can theoretically capture the full taxonomic breadth of the eDNA pool. However, eukaryotic DNA is often a small component of metagenomes; consequently they have seen limited use in metazoan biodiversity surveys. Here, we compare metabarcoding and shotgun metagenomes on a large (>200 sample size) set of marine water column eDNA samples and show that metagenomes can provide biodiversity information comparable to that of metabarcoding surveys. They provide more consistent and even detections of important phytoplankton like chlorophytes and haptophytes and can detect metazoan taxa of management and conservation interest, such as the humpback whale. However, genus- and species-level taxonomic assignments are often inaccurate for metagenomic data and require more manual annotation relative to metabarcoding taxonomy. Reference database gaps remain an obstacle to accurate and comprehensive biodiversity surveys for both metabarcoding and shotgun metagenomes. We provide examples of taxa that may benefit from one approach over another and highlight cases of metagenomic utility.